Crystallization and preliminary X-ray diffraction analysis of a myotoxic phospholipase A(2) homologue from Bothrops neuwiedi pauloensis venom - Fontes, MRM; Soares, A. M.; Rodrigues, V. M.; Fernandes, A. C.; Da Silva, R. J.; Giglio, JR (Elsevier B.V., 1999)
Crystals of a myotoxic phospholipase A(2) from Bothrops neuwiedi pauloensis have been obtained. They diffracted at 2.5 Angstrom resolution using a synchrotron radiation source and belong to space group P3(1)21. Preliminary analysis shows that there are two molecules in the asymmetric unit. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: crystallization; Lys-49 myotoxin; phospholipase A(2); snake venom